Comparison of small multirotor wake vortex of different weight class and rotor configurations via numerical simulation - Wang, John Chung-Hung (2023)
Wake hazard is one of the factors affecting the separation requirement for same-track fixed-wing aircraft in civil aviation. It could also be a contributing factor for UAS traffic management (UTM) with multirotors, especially with the widespread use of ADS-B like remoteID for UAS that greatly reduces the separation requirements due to communication, navigation, and surveillance (CNS) performance of the aircraft and the airspace. While the wake vortex structure and decay mechanism for fixed-wing aircraft has been well studied over the years, the same dynamics might not be observed in multirotor aircraft due to difference in lift generation mechanism. Additionally, the difference in wake vortex generation from different multirotor configurations were not as well studied. This paper presents the simulation results from two quadrotors (DJI Phantom 3 size, ~ 1.2 kg and Inspire 1 size, ~ 3.5 kg) and one hexarotors (DJI M600 sized, ~ 15 kg) for a fixed follow distance behind those aircraft.